Enhancing Elementary School Teachers’ Competence through Adaptive Mathematics Materials for Children with Down Syndrome - Sulistyani, Umi (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to strengthen elementary school teachers’ competence through the use of adaptive mathematics materials for children with Down syndrome. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The development process was based on a needs analysis conducted in two special education schools, namely SLB BC Mahardika Depok and SLB BC Abdi Pratama Munjul. The adaptive mathematics materials focus on number recognition (1–20), addition and subtraction (1–9), and time concepts, presented through illustrated and colorful learning materials tailored to the characteristics of children with Down syndrome. Product validation was carried out by material experts and design experts using questionnaire instruments. The validation results showed high feasibility levels, with material expert scores of 97.5% and 91.25%, and a design expert score of 93.33%, all categorized as good and appropriate. These findings indicate that the developed adaptive mathematics materials are feasible to support teachers in delivering inclusive mathematics instruction and enhancing their professional competence in teaching children with Down syndrome